Development of Chemical Bonding Module Based on Multiple Representation - Auzan Qashdi; Susilawati Susilawati; R. Usman Rery (Journal of Educational Sciences, 2022)
This study aims to develop a valid chemical bonding material module and can be used as independent learning materials for students in learning activities. This study is based on teaching materials used in some schools, representation of the phenomenon used only macroscopic and symbolic, while submicroscopic phenomenon has not been seen in the teaching materials used and some teachers have just heard the term. This study uses model of research and development Plomp. Data collection techniques in research are validation sheet, teacher response questionnaire, and student response questionnaire. The results of data analysis obtained validity on the aspect of content feasibility, linguistic aspect, presentation aspect, graphic aspect, and characteristics aspect of multiple representation validated by three validators, respectively for 97.14%, 89.52%, 93.33%, 95.24%, and 97.78% with valid categories. Evaluation result of small group was taken teacher response and learner response as user of chemical bond module based on multiple representation. looking at the questionnaire of teacher's response to the chemical bond module based on multiple representation, the average score was 90.22% with very good categorization. Questionnaire response of students to chemical bonding module based on multiple representation is 89.37% with good categorized.